The impact of watching English movies on students’ listening comprehension - Hendra Wicaksono; Diego Javier Romero (Early Publishing Group, 2026)
This study explores the impact of watching English movies on students' listening comprehension, a vital skill for effective communication in a globalized world. Understanding spoken English remains a significant challenge for second language learners due to factors such as speech rate, accents, connected speech, and idiomatic expressions. While previous research has highlighted the benefits of audiovisual resources in language learning, there is limited empirical evidence specifically examining how structured exposure to English films influences listening proficiency within classroom settings, especially among non-native speakers. This research aims to fill this gap by evaluating the effectiveness of English movies as a pedagogical tool to enhance listening skills. The study employed a quasi-experimental design involving 60 intermediate-level EFL students from a private university, who were randomly assigned into experimental and control groups (30 participants each). Data were collected through pre- and post-intervention listening tests, along with questionnaires measuring viewing frequency outside the classroom. The listening assessments focused on overall comprehension and recognition of informal language features. Data analysis included descriptive statistics, t-tests for comparing group performances, and correlation analyses to examine the relationship between viewing frequency and listening improvements. The key findings reveal that students exposed to English movies demonstrated significantly greater gains in listening comprehension compared to those receiving traditional instruction. Furthermore, there was a positive correlation between the frequency of movie watching and the extent of listening improvement, indicating that sustained exposure enhances comprehension. These results suggest that integrating authentic media resources like movies into ESL instruction can effectively improve listening skills by providing real-life language input, exposure to diverse accents, and natural speech patterns.